The Authenticity of Cultural Ways of Life: A Hermeneutic of the Ifugao Social Practice Gotad - Joernie Mar U. Bistol (Religion and Social Communication)
This study examines the Ifugao Gotad cultural practice to distinguish the valued transcendent meaning and the normative values that are faithfully lived. It builds on Ginev’s hermeneutic theory of social practices that determines the nexus of authenticity in human agency participating in configured practices. It is argued that an integral and authentic identity is achieved through reflexive appropriation of possibilities in routinized practices of everyday life and heeding the call of the cultural lifeform’s transcendent authority. In doing so, the study first shows how a hermeneutic of social practices provides an explanatory view of our culture. Second, the study examines how the hermeneutic of social practices allows the determination of human subjectivity and the cultural lifeform as existentially authentic or inauthentic. Lastly, a hermeneutic of the Ifugao cultural Gotad practice reveals the authenticity of the cultural lifeform through the members heeding the call of its transcendent meaning and authority. The reconfiguration of the traditional Ifugao Gotad practice into an institutionalized ethnocultural thanksgiving gathering represents the contemporary Ifugao cultural way of life, re-establishes and recontextualizes the people’s agency in the face of competing ways of life, encourages the people to continue to find ways of ensuring their well-being, allows the members to resolve tensions arising from conflicting ways of life, and rediscover their cultural rootedness.